Comparative literature study between investigations in foreign Sci- ence Citation Index journals and Chinese core domestic journals in the treatment of low back pain with acupuncture - Xiangjun Lin Rui Li (中医杂志：英文版, 2014)
OBJECTIVE： To investigate the quality and meth- ods of clinical research literature published in for- eign Science Citation Index （SCI） journals studying the treatment of low back pain with acupuncture. To conduct a comparative study with clinical re- search literature published in Chinese core domes- tic journals, and to understand the prospects of cur- rent research trends of acupuncture clinical studies in Western countries and China. METHODS： Studies on clinical acupuncture treat- ment of low back pain in English SCI journals and four Chinese core domestic journals dated from 2002 to 2012 were sourced and summarized for this study. Objective analysis and evaluation on the differences in subject and scope of study on low back pain by foreign and Chinese researchers were conducted. RESULTS： Forty-seven English studies and 115 Chi- nese studies met our inclusion criteria. A keyword search revealed different kinds of low back pain re- lated conditions in English and Chinese studies. The English studies were broad in scope, while the Chinese studies were more focused. There were al-so differences in the understanding and definition of concepts and study orientation. CONCI.IJSION： More study should be undertaken to understand the contradictions that acupuncture faces in view of modern research to further ad- vance the field.